Deux perspectives pour analyser les relations professionnelles - John T. Dunlop; William F. Whyte; Arnaud Mias (La Nouvelle Revue du Travail)
This article appeared in Industrial and Labor Relations Review, following an early 1949 meeting at Princeton University between William Foote Whyte (1914-2000) and John Thomas Dunlop (1914-2003) to debate an industrial relations analysis framework, this being a heavily studied topic in the United States at the time. The controversy between a leader of the “human relations” school of thought that was on the rise at the time, and one of the main figures in the field of industrial relations, revealed the two directions between which US industrial relations’ theoretical development was hesitating. The main question was whether industrial relations constituted a natural extension of a framework for analysing human relations with a view towards improving understanding how unions and managements interact – or whether they had other theoretical or methodological foundations capable specifically of measuring how context and economic, social, political and technical conditions influence what happens inside a company. The debate nourrished thinking about different categories of reflection and action while augmenting understanding of collective bargaining’s increasing decentalisation towards companies.